Association between intraoperative tidal volume and postoperative respiratory complications is dependent on respiratory elastance: a retrospective, multicentre cohort study. (August 2022) - Suleiman, Aiman; Costa, Eduardo; Santer, Peter; Tartler, Tim M.; Wachtendorf, Luca J.; Teja, Bijan; Chen, Guanqing; Baedorf-Kassis, Elias; Nagrebetsky, Alexander; Vidal Melo, Marcos F.; Eikermann, Matthias; Schaefer, Maximilian S.
Abstract: Background: The impact of high vs low intraoperative tidal volumes on postoperative respiratory complications remains unclear. We hypothesised that the effect of intraoperative tidal volume on postoperative respiratory complications is dependent on respiratory system elastance. Methods: We retrospectively recorded tidal volume (Vt; ml kg −1 ideal body weight [IBW]) in patients undergoing elective, non-cardiothoracic surgery from hospital registry data. The primary outcome was respiratory failure (requiring reintubation within 7 days of surgery, desaturation after extubation, or both). The primary exposure was defined as the interaction between Vt and standardised respiratory system elastance (driving pressure divided by Vt; cm H2 O/[ml kg −1 ]). Multivariable logistic regression models, with and without interaction terms (which categorised Vt as low [Vt ≤8 ml kg −1 ] or high [Vt >8 ml kg −1 ]), were adjusted for potential confounders. Additional analyses included path mediation analysis and fractional polynomial modelling. Results: Overall, 10 821/197 474 (5.5%) patients sustained postoperative respiratory complications. Higher Vt was associated with greater risk of postoperative respiratory complications (adjusted odds ratio=1.42 per ml kg −1 ; 95% confidence interval [CI], 1.35–1.50]; P <0.001). This association was modified by respiratory system elastance ( P <0.001); in patients with low compliance (<42.4 ml cm H2 O −1 ), higher Vt was associated with greater risk of postoperative respiratory complications (adjusted risk difference=0.3% [95% CI, 0.0–0.5] at 41.2 ml cm H2 O −1 compliance, compared with 5.8% [95% CI, 3.8–7.8] at 14 ml cm H2 O −1 compliance). This association was absent when compliance exceeded 41.2 ml cm H2 O −1 . Adverse effects associated with high Vt were entirely mediated by driving pressures ( P <0.001). Conclusions: The association of harm with higher tidal volumes during intraoperative mechanical ventilation is modified by respiratory system elastance. These data suggest that respiratory elastance should inform the design of perioperative trials testing intraoperative ventilatory strategies.